Ullmann's Encyclopedia of Industrial Chemistry 2010
DOI: 10.1002/14356007.n05_n01
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, 2. Diamond

Abstract: The article contains sections titled: 1. Properties and Structure of Natural Diamond 2. Diamond Synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The global warming impacts of DND and synthetic diamond grit can be compared because they have similar properties and are used in similar applications, such as polishing. , Specifically, the impact of 1 g DND (baseline scenario in this study) was compared to 1 g synthetic diamond grit (HPHT production according to the “current scenario” in Furberg et al). The comparison shows that the global warming impact of synthetic diamond grit (about 920 g CO 2 equiv/g) is about 5 times higher than the impact of DND (about 180 g CO 2 equiv/g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global warming impacts of DND and synthetic diamond grit can be compared because they have similar properties and are used in similar applications, such as polishing. , Specifically, the impact of 1 g DND (baseline scenario in this study) was compared to 1 g synthetic diamond grit (HPHT production according to the “current scenario” in Furberg et al). The comparison shows that the global warming impact of synthetic diamond grit (about 920 g CO 2 equiv/g) is about 5 times higher than the impact of DND (about 180 g CO 2 equiv/g).…”
Section: Resultsmentioning
confidence: 99%
“…Diamond film production via MWCVD utilizes gas as a precursor, consisting of methane (CH 4 ) and hydrogen (H 2 ) from which carbon is deposited onto a substrate . Large-scale commercialized diamond film production is typically conducted using a 915 MHz operating frequency apparatus with a power of 30–60 kW accommodating a substrate of about 15 cm in diameter . The diamond film growth rate is 1–12 μm/h depending on the application .…”
Section: Calculationsmentioning
confidence: 99%
“…All gas flows were controlled by mass flow controllers. The temperature for all experiments was 1000°C and the reaction time 4 h. Chlorination took place at a chlorine concentration of 2.5 mol m The conversion was determined gravimetrically 1) :…”
Section: Chlorinationmentioning
confidence: 99%
“…In particular activated carbon is used for a number of applications such as treatment of sewage or purification of gases [1]. In catalysis porous carbons are used either as active or inert supports.…”
Section: Introductionmentioning
confidence: 99%
“…According to work by the Henning group about the study on the mechanical behavior of an extruded mixture during carbonization, the specimen exhibited viscoelastic behavior at temperatures below the resolidification temperature of binder pitch (∼770 K) and ideal elastic behavior at temperatures above it. It is generally accepted that the porosity that developed below 673 K is mostly due to an important release of volatile matter from the fluid, but highly impervious binder pitch tends to increase the internal pressure inside the green body . In that respect, the formation of porosity depends basically on kinetic considerations; that is, the rate of formation of volatiles must be comparable to or lower than the rate of their diffusion outside the green body. It was analyzed that the internal pressure and the thermal stress were main factors that limit heating rates, and the result showed that both the gas pressure and the stress from the gas pressure increase approximately in proportion to specimen diameter and square root of heating rate.…”
Section: Introductionmentioning
confidence: 99%